الاستصحاب عند الأصوليين وأثره في فقو العبادات)نماذج مختارة - العايب, ابراهيم; قيطون, الخير; تارش, الطاهر (جامعة الوادي - University of Eloued, 2019)
يعتبر الاستصحاب من الأدلة الدهمة التي يَستدل بها الفقهاء كثتَاً، وىو: "استدامَةُ إثباتِ مَا كانَ ثابتاً أو نَ فْيِ فيِ مَا كان منفي اً حتى يأتي الدليل الدغتَ لتلك الحالة " وىو آخر دليل يلتجئ إليو الدفتي. وقد حاولنا من خلال ىذه الدارسة الإحاطة بأكثرِ الأحكام النظرية الدتعلقة بالاستصحاب من:تعريفو، مكانتو، أنواعو، حجيتو، بعض الدسائل الدتعلقة بو؛ كما قمنا بدراسة بعض الشواىد التطبيقية لدليل الاستصحاب في قسم فقو العبادات، وقد اتبعنا الدنهج الوصفي التحليلي، وتوصلنا في آخر الدراسة لعدة نتائج منها: - أن الاستصحاب لا يثبت حكما بنفسو بل يدل على بقاء الحكم الثابت من قبل. - أن الاستصحاب من الأدلة التي يكثر استثمارىا في كل أبواب الفقو مما يدل على أنذيتو، وكثرة الحاجة إليو. - أن الاستصحاب يعد دليلا مواكبا للمستجدات الفقهية التي تقع في شتى الأزمنAccompanying is considered one of the proofs that scholars use a lot. And it is sustaining what is fixed and denying what should be denied until there is a found evidence of change for a certain case. And it is the last evidence that the interpreter takes . We have tried throughout this study to embrace most of the the oritical verdicts that has something to do with accompanying from definition , its place , kinds , its evidence and some stuff that are related to it as well as we have studied some practicable statistics for the sake of finding the accompanying in the class of latest fikh updates . Also we have followed the approach of describing and Analysing and we have reached in our study so many results such as : - That withdrawal does not turn to be verdict itself but it signifies the staying of the verdict that is earlier fixed . و - Accompanying is one of the evidences that is mostly used in all the fikh doors and this shows its importance and how needed it is . - Accompanying is an evidence that is considered to be occurring at the same time.
مذكرة ليسانس
Keywords: الاستصحاب/ الاصولين /فقه العبادات; Istishab / fondamentalistes / jurisprudence du culte